2007
DOI: 10.1111/j.1399-3046.2007.00681.x
|View full text |Cite
|
Sign up to set email alerts
|

The challenges of using medication event monitoring technology with pediatric transplant patients

Abstract: This study investigated the advantages and challenges of using Medication Electronic Monitoring System (MEMS) technology to examine adherence among pediatric kidney transplant patients. Twenty-nine patients participated in the study, with a mean age of 14.03 yr (SD = 3.34, range 8-19 yr). Patients were given a MEMS bottle and cap to be used with their primary immunosuppressant medication over a three-month period. Issues related to study eligibility, recruitment, and participant maintenance were recorded. Pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 16 publications
(44 reference statements)
3
49
0
Order By: Relevance
“…Whereas we found that the MEMS-bottle was readily accepted by patients on ART, other studies found that some patients, especially those who prefer not to disclose their HIV-status, do not like the white, bulky appearance of the MEMS for privacy concerns [18-20]. The high acceptability of MEMS-use by patients in the current study is particularly remarkable because fears of disclosure of one's HIV-status and consecutive stigmatization are widely present in Tanzania and patients prefer to carry their medication as discretely as possible [21,22].…”
Section: Discussionmentioning
confidence: 83%
“…Whereas we found that the MEMS-bottle was readily accepted by patients on ART, other studies found that some patients, especially those who prefer not to disclose their HIV-status, do not like the white, bulky appearance of the MEMS for privacy concerns [18-20]. The high acceptability of MEMS-use by patients in the current study is particularly remarkable because fears of disclosure of one's HIV-status and consecutive stigmatization are widely present in Tanzania and patients prefer to carry their medication as discretely as possible [21,22].…”
Section: Discussionmentioning
confidence: 83%
“…18 On the other hand, objective methods, such as pill counts or electronic monitoring, frequently impose additional burden on the patient, and may require significant logistic support. 19,20 Increased patient burden matters because nonadherent patients are not likely to cooperate with a procedure that increases their burden. A patient who finds it hard to take the medications as prescribed, will probably also find it hard to bring the pill bottle to clinic, or use an electronic monitor.…”
Section: Introductionmentioning
confidence: 99%
“…A patient who finds it hard to take the medications as prescribed, will probably also find it hard to bring the pill bottle to clinic, or use an electronic monitor. 19,20 Resource-allocation barriers as well as difficulties in engaging the very segment of the population that should be monitored, 20 limits the use a robust adherence monitoring plan. 18, 21, 22 There is particular interest in identifying simple objective methods allowing efficient targeting of at-risk patients via algorithms built into standard care.…”
Section: Introductionmentioning
confidence: 99%
“…MEMS® technology provides continuous data and allows for the detection of temporal patterns of adherence. Yet, barriers associated with MEMS® technology include cost and the possibility that these devices may interfere with established adherence-promoting routines, such as the use of pillbox organizers (19). …”
Section: Assessment Of Medication Adherence In Transplantationmentioning
confidence: 99%